Hyalinizing clear cell carcinoma of the head and neck: Case series and update. Issue 3 (18th June 2015) - Albergotti, W. Greer; Bilodeau, Elizabeth A.; Byrd, J. Kenneth; Mims, Mark M.; Lee, Stella; Kim, Seungwon
Abstract: Background: Hyalinizing clear cell carcinoma (HCCC) is a rare neoplasm of salivary gland origin which is low‐grade in nature. In this series, we report on 9 cases of HCCC and update the literature. Methods: A comprehensive literature search was performed. Our institutional database was queried for cases of HCCC. Pathology reports and slides were reviewed. Data was extracted, including demographics, staging, primary treatment, histopathologic findings, recurrence, and disease status. Statistical analysis was performed using a Pearson's chi‐square test. Results: One hundred thirty‐six total cases were included for analysis. The overall recurrence rate was 19.8%. Necrosis was associated with risk of recurrence ( p = .003). Positive margins and lymph node status were associated with risk of recurrence. Prognosis was good with only 3 of 82 patients reported dying with disease. Conclusion: HCCC has an overall good prognosis with potential for aggressive behavior. The presence of necrosis, locoregional disease, or positive margins is associated with risk for recurrence. © 2015 Wiley Periodicals, Inc. Head Neck 38: 426–433, 2016